Metabolic studies of Ogataea polymorpha using nine different corn steep liquors - Sekar Mayang W. Wahjudi; Dominik Engel; Jochen Büchs (BMC Biotechnology)
Abstract Background In the fermentation industry, the demand to replace expensive complex media components is increasing for alternative nutrient sources derived from waste or side streams, such as corn steep liquor (CSL). However, the use of CSL is associated with common problems of side products, such as batch-to-batch variations and compositional inconsistencies. In this study, to detect batch-to-batch variations in CSL for Ogataea polymorpha cultivations, a “fingerprinting” system was developed by employing the Respiration Activity Monitoring System designed for shake flasks (RAMOS) and 96-well microtiter plates (µTOM). Results At 2.5 g d.s./L CSL and 5 g/L glucose, a limitation by a secondary substrate, other than the carbon source, was observed. For this specific CSL medium, this limitation was caused by ammonium nitrogen and could be removed through targeted supplementation of ammonium sulphate. Under ammonium nitrogen limitation, O. polymorpha showed a change in morphology and developed a different cell size distribution. Increasing CSL storage times impaired O. polymorpha cultivation results. It was speculated that this observation is caused by micronutrient precipitation as sulfide salts. Through targeted nutrient supplementation, these limiting microelements were identified to be copper, iron and zinc. Conclusions This study shows the versatility of CSL as an alternative nutrient source for O. polymorpha cultivations. “Fingerprinting” of CSL batches allows for early screening. Fermentation inconsistencies can be eliminated by selecting the better performing CSL batches or by supplementing and improving an inferior CSL prior to large-scale productions.